Gender differences on methadone maintenance treatment outcome among patients with opioid use disorder: A systematic review - Mohemmad Redzuan Mohemmad Rizal; Amer Hayat Khan; Sabariah Noor Harun; Zaiton Saleh (Wolters Kluwer Medknow Publications, 2020)
Objectives: The objective of this study was to review the significant differences of MMT outcomes related to drug use behavior, health status, and social behavioral functioning between genders. Materials and Methods: A search of publication was conducted in PubMed/MEDLINE, Embase, CINAHL, PsycINFO, and Scopus database. Two reviewers independently screened the titles, abstracts, and keyword use for the search. Inclusion of studies was based on randomized controlled trials (RCTs) or observational studies that report the difference of opioid addiction treatment outcomes between genders. Any conflict between the two reviewers was resolved through discussion and consensus. The systematic review followed the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines and was registered in PROSPERO with a registration number CRD42019116261. Results: A total of 25 studies were evaluated as part of qualitative synthesis. The review resulted in three main themes, which are (1) improving well-being and methadone-related outcome (five subthemes), (2) impact on social and behavioral (four subthemes), and (3) illicit drug use pattern-related behavior (four subthemes). Conclusion: This review will highlight how men and women differ in methadone treatment outcomes for further application and improvement in the clinical setting.